Generalized semicommutative and skew Armendariz ideals - Nikmehr, M.J. (Український математичний журнал, 2014)
We generalize the concepts of semicommutative, skew Armendariz, Abelian, reduced, and symmetric left ideals and study the relationships between these concepts.